HOW VIETNAMESE UNDERSTANDS ABOUT DECENTRALIZATION: AN Q- METHODOLOGY STUDY - Ngoc Minh, Windy Thi (PEOPLE: International Journal of Social Sciences, 2018)
Nowadays, more and more countries move away from centralized governments institutions. Decentralized government institutions are doing more work of government both in developed and developing countries than ever before. The literature on decentralization are vast, but there is little agreement about what decentralization means. There are not many research about the conceptualization of the decentralization in Vietnam. Official decentralization in Vietnam began with Doimoi (economic innovation) in 1986 and rapidly accelerated in late 1990. How the citizens understand the decentralization to develop their power to construct a nation. The aim of this study is finding out what Vietnamese citizens comprehend about decentralization, especially the intellectual class because of the critical role of this class in society. This study's participants were a sample of 17 people from intellectual class who had education level at least bachelors' degree in Ho Chi Minh City – the largest, the developed city in South of Vietnam. Q- methodology, which was introduced by William Stephenson in 1935, was used for data collection and analysis. Four distinct viewpoints about decentralization were identified: (1) democratization, (2) Public-private transfer, (3) Theoretic Stereotype and (4) A comprehensive view. This study also finds out that maybe Vietnamese are emphatically agreed that decentralization is the transfer of authority and general definition and administrative decentralization are paid attention.